Environmental metabonomics applying combination biomarker analysis in earthworms at a metal contaminated site - Bundy, Jacob G (Ecotoxicology (London, England), 2004)
Earthworms were taken across an environmental gradient of metal contamination for ecotoxicology assessment. Both indigenous (Lumbricus rubellus and L. terrestris) and introduced earthworms (Eisenia andrei, exposed in mesh bags) were studied. Changes in the levels of small molecule metabolites in earthworm tissue extracts were analysed by 1H NMR spectroscopy as a means of identifying combination biomarker compounds. Principal components analysis of the NMR spectral data revealed that biochemical changes were induced across the metal contamination gradient. Native worms (L. rubellus) from the most polluted sites were associated with an increase in the relative concentration of maltose; a decrease was also seen in the concentration of an as yet unidentified biomarker compound. Introduced worms (E. andrei) did not show differences to the same extent. Direct integration of the resonances from histidine and 1-methylhistidine showed that relative histidine concentrations were elevated slightly for L. rubellus, confirming the results of earlier mesocosm studies. Conversely, the relative concentrations of both histidine and 1-methylhistidine were greatly reduced by metal contamination in L. terrestris. This study demonstrates the utility of NMR spectroscopy in detecting previously unknown potential biomarkers for ecotoxicity testing and identified maltose as a potential biomarker compound deserving of further study